Child protection: A handbook for parliamentarians - Anders B. Johnsson, Carol Bellamy (2016)
The handbook includes examples of the many ways in which Parliaments and their members around the world have responded to the challenges of child protection through laws, policies, advocacy and other means. It also describes how Parliaments and their members can gain a clearer understanding of what their contribution can be, and equips them with the knowledge and tools they require to make that contribution.